Entrepreneurial Orientation and Market Innovativeness among Small and Medium Enterprises in Nigeria (Lapai Journal of Economics, 2019)
The study investigates entrepreneurial orientation and marketing innovativeness among SMEs in Nigeria with the specific objectives of evaluating the association between risk taking and technological innovativeness; determining the impact of pro-activeness on product innovation. The study was conducted among SMEs in Ijebu-Ode Local Government Area, Ogun State. The study adopted the survey design and the data were analysed using linear and t-test methods of data analyses. Structured questionnaire was employed to collect data from respondents. The primary data generated from the questionnaire were used to verify the formulated hypothesis. A total of 140 questionnaires were administered. Results revealed that there was significant relationship between risk-taking and technological innovations. The implication therefore is that entrepreneurs should ensure they take calculated risk in order to enhance their productivity through innovation and that there was need for them to be proactive in their approach to product development as this could improve their quality and productivity.